The difference in artificial grass and natural grass in Icelandic football - Jóhann Ægir Arnarsson 2002- (2024)
Objective: To see if the percentage of wins, draws, and losses are associated with the type of surface and/or the type of surface the away team plays on at home. To see if there is a significant difference in FH football club men ́s first team games both attacking wise and defensive wise when FH plays at home against teams that play their home games on artificial grass compared to teams that play their home games on natural grass. Lastly, if there is a significant difference in FH games both attacking wise and defensive wise when FH plays away against teams that play their home games on artificial grass compared to teams that play their home games on natural grass. Method: Raw data from the 2023 season in Besta deildin (Iceland ́s premier men ́s league) was ran into SPSS to look at the percentages of wins, draws, and losses. I also looked at data from FH games and compared the means, and standard deviation which was gathered from a T-test, as well as looking at the results from the independent sample T-test from the variables that were taken into consideration Results: The percentage of wins, draws and losses depend on the type of surface the game is played on and on what kind of surface that away team plays on at home. There is a significant difference between games both attacking wise and defensively when FH plays at home compared to teams that play their home games on artificial grass compared to teams that play their home games on natural grass. There is a significant difference between games both attacking wise and defensively when FH plays away, to teams that play their home games on artificial grass compared to teams that play their home games on natural grass.